Problematizando os “manuais do professor” de história sob a perspectiva da inclusão do outro - Fonseca, Renan Donizete (2017)
In this research, it was proposed to analyze and problematize the orientations given to teachers through the Teacher Manual versions of the textbooks of History in relation to the inclusion of the other, a concept intricate in the Habermasian political theory, that defends the democratic host of the different, thinking here in an expanded way, by different subjects that flee from a model considered standard. For this, it is intended to deepen within the thoughts of inclusion within the democratic theory present in the diverse thinkers of democracy.The development of this research will enable the problematization, based on the perspective of gender studies, which is more concerned with the questions that can be asked to a particular text, than the answers to be found. The problematization will occur based on the qualitative analysis of the contents and the orientations to the teachers present in these versions dedicated to the teachers of the textbooks, and whose orientations can meet the presuppositions of promoting the inclusion of these "others" within the democracy. Think about education as an instrument for strengthening democracy itself, and History Teaching in this context. It is also intended to articulate in this analysis the pertinent discussions on the following topics: democracy, history teaching, textbook and identity. Finally, in this work when articulating these various attempts, it is effort to understand the articulating possibilities among philosophy, sociology, history and education for the understanding and study of the school writings pointed out to teachers.